2019
DOI: 10.21037/atm.2019.12.64
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Lonicera japonica polysaccharide on mice with depression by inhibiting NLRP3 inflammasome

Abstract: Background: Depression is associated with the abnormal activation of the human inflammatory response system, which is a life-threatening disorder affecting millions of people of all ages around the world. The purposes of the present study were to examine the effect of Lonicera japonica polysaccharide (LJP), a polysaccharide extracted from Lonicera japonica Thunb., on depressed mice treated with the unpredictable emotional stress stimulation. Methods: The components of LJP after extraction were detected by HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…IGF1, acts as a ligand for IGF1R, activated the PI3K-AKT [59] and Ras-MAPK [6] pathways. PIK3R1 and AKT1 were the key proteins of the PI3K-AKT [59] pathways which regulate apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF1, acts as a ligand for IGF1R, activated the PI3K-AKT [59] and Ras-MAPK [6] pathways. PIK3R1 and AKT1 were the key proteins of the PI3K-AKT [59] pathways which regulate apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no specific drugs for the clinical treatment of IS. Most of the drugs used for treatment are drugs that protect against free radical damage, thrombolytic drugs, antiplatelet aggregation drugs, anti-inflammatory drugs, and anticoagulants [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, animal models displayed anxiety and depression-like behavior and memory loss symptoms. Suppressing the activation of the NLRP3 inflammasome exerted neuroprotective effects and improved the aforementioned neurological symptoms ( Lu et al, 2014 ; Zhang et al, 2014 ; Xu et al, 2016 ; Liu et al, 2019 ; Fu et al, 2020 ; Li et al, 2020 ). In addition, several recent studies have shown that the NLPR3 inflammasome is involved in the pathogenesis of neuropathic pain, and inhibition of NLPR3 inflammasome can effectively alleviate nociceptive hypersensitivity ( Jia et al, 2017 ; Zhang et al, 2017 ; Grace et al, 2018 ; Khan et al, 2018 ; Pan et al, 2018 ; Chen et al, 2019a , 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that polysaccharides extracted from plants can relieve oxidative stress through exerting their antioxidation potentials ( Surin et al, 2018 ; Zhou et al, 2020 ). Polysaccharide is one of the main active ingredients of L. japonica , which have been isolated and identified in previous studies ( Zhou et al, 2018a , 2020 ; Liu et al, 2019 ; Zhang T. et al, 2020 ). In vitro study showed that polysaccharide extracts from L. japonica exhibited obvious DPPH-scavenging activity, ABTS + -scavenging activity, hydroxyl radical-scavenging activity, superoxide radical-scavenging activity, and excellent inhibitory activity on erythrocyte hemolysis induced by H 2 O 2 ( Zhang T. et al, 2020 ).…”
Section: Lonicera Japonica (Extracts) and Intestinal Antioxidantmentioning
confidence: 99%